2022
DOI: 10.1039/d2dt02040h
|View full text |Cite
|
Sign up to set email alerts
|

Targeted cancer phototherapy using phthalocyanine–anticancer drug conjugates

Abstract: Phototherapy, the use of light to selectively ablate cancerous tissue, is a compelling prospect. Phototherapy is divided into two major domains: photodynamic and photothermal, whereby photosensitizer irradiation generates reactive oxygen...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…Due to its proper aromatic rings created by nitrogen atoms, it's frequently used to stain several biomolecules and it has quite absorption and emission properties [44]. Furthermore, novel approaches are using Phthalocyanine in the phototherapy treatment of tumors [45]. In addition, while there is no evidence pointing the interactions of Phthalocyanine with Cat D in literature, ligandprotein interaction analysis has shown that Phthalocyanine might interact with Cat D's ALA 13, ILE 134, MET 307, and MET 309 residues through pi-sulfur and pi-alkyl interactions, ASP 231 residue through pi-anion interactions.…”
Section: Resultsmentioning
confidence: 99%
“…Due to its proper aromatic rings created by nitrogen atoms, it's frequently used to stain several biomolecules and it has quite absorption and emission properties [44]. Furthermore, novel approaches are using Phthalocyanine in the phototherapy treatment of tumors [45]. In addition, while there is no evidence pointing the interactions of Phthalocyanine with Cat D in literature, ligandprotein interaction analysis has shown that Phthalocyanine might interact with Cat D's ALA 13, ILE 134, MET 307, and MET 309 residues through pi-sulfur and pi-alkyl interactions, ASP 231 residue through pi-anion interactions.…”
Section: Resultsmentioning
confidence: 99%
“…Phthalocyanines, as a series of classical photosensitizers, have been widely concerned in PDT, but they still have the drawbacks of high phototoxicity and poor selectivity [ 50 ] Therefore, based on phthalocyanine molecules and nanosized phthalocyanines, the strategy of using activatable phthalocyanines can significantly improve the selectivity and reduce phototoxicity of phthalocyanines. [ 51 ] Activatable strategy means that the activity of phthalocyanine in healthy tissues is inhibited, and the activity is restored under the stimulation of various factors (such as pH, enzyme, nucleic acid, GSH).…”
Section: Design Strategiesmentioning
confidence: 99%
“…In the type-II mechanism, a tripletexcited photosensitizer reacts with molecular oxygen to give highly reactive singlet oxygen, 1 O 2 , as reactive intermediate, which in turn oxidizes the DNA bases [46]. As a result, various classes of photosensitizers [47][48][49] have been established, for example, porphyrins [50], chlorins [51], phthalocyanines [52], porphycenes [53], metal-organic complexes [54][55][56], dye aggregates [57], as well as nano-drug carriers and metal-based nanoparticles [58,59]. But although these classes of compounds have been intensively studied and already contributed significantly to the field of PDT, there is still a demand for novel DNA-photodamaging ligands that could be applied for specific purposes, e.g., to improve efficacy or to limit side-effects.…”
Section: Introductionmentioning
confidence: 99%